COI barcodes for ants (Hymenoptera: Formicidae) of drylands in the south of Ecuador [Códigos de barras (COI barcodes) para hormigas (Hymenoptera: Formicidae) de los bosques secos del sur del Ecuador] - Donoso Vargas, D. (2016)
We provide metadata for 110 COI barcodes for a collection of 38 ant species from Alamala, Laipuna, El Chilco, and Reserva Ecológica Arenillas (REA) in the south of Ecuador, sampled as part of ecological and taxonomical research on ant communities of Ecuadorian drylands. This paper contributes to the International Barcode of Life (iBOL) project, and aims to make DNA barcode data available to encourage species identifications by the scientific community. We facilitate Genbank accession numbers and assembled metadata (i.e. images, coordinates) through DOI dx.doi.org/10.5883/DS-DRYLOJA. This publication reports the following species for the first time in continental Ecuador: Camponotus conspicuus zonatus (Emery 1894), Crematogaster torosa (Mayr 1870), Dorymyrmex pyramicus peruvianus (Wheeler 1919), Neivamyrmex iridescens (Borgmeier 1950), and Pseudomyrmex kuenckeli (Emery 1890). © 2016 Los Autores.